Fractional Order PD and PID Position Control of an Angular Manipulator of 3DOF - Rojas Moreno, Arturo (2013)
This paper deals with the implementation of two position control systems: FOPID (Fractional Order Proportional Integral Derivative) and FOPD (FO Proportional Derivative), which are employed to control simultaneously angular positions of the base, arm, and forearm of an angular manipulator of 3DOF (3 Degrees of Freedom). Intensive simulation studies, using the dynamic nonlinear model of the angular manipulator as well as the designed control laws, permitted to determine the initial values of the tuning parameters of the FOPD and FOPID controllers for real time implementation. Good performances of the designed control systems were verified via experimentation.